2019
DOI: 10.2196/14924
|View full text |Cite
|
Sign up to set email alerts
|

A Serious Game–Derived Index for Detecting Children With Heterogeneous Developmental Disabilities: Randomized Controlled Trial

Abstract: BackgroundDevelopmental disabilities are a set of heterogeneous delays or difficulties in one or more areas of neuropsychological development. Considering that childhood is an essential stage of brain development and developmental delays lead to personal or social burdens, the early detection of childhood developmental disabilities is important. However, early screening for developmental disabilities has been a challenge because of the fear of positive results, expensive tests, differences in diagnosis dependi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 34 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…In addition, games, digital games, educational games, and video games, together, are the second most used set of author keywords. It can be inferred from this finding that the term "serious game" has been used in the majority of articles, especially in recent years (Bang et al, 2019;Faria et al, 2019;García-Redondo et al, 2019;Jaramillo-Alcázar et al, 2020;Lievense et al, 2019;Ronimus et al, 2020;Tang et al, 2019). Based on the bibliometric results, disability and rehabilitation are also among the most used author keywords.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition, games, digital games, educational games, and video games, together, are the second most used set of author keywords. It can be inferred from this finding that the term "serious game" has been used in the majority of articles, especially in recent years (Bang et al, 2019;Faria et al, 2019;García-Redondo et al, 2019;Jaramillo-Alcázar et al, 2020;Lievense et al, 2019;Ronimus et al, 2020;Tang et al, 2019). Based on the bibliometric results, disability and rehabilitation are also among the most used author keywords.…”
Section: Discussionmentioning
confidence: 95%
“…Based on the findings of this study, the majority of the articles used quantitative methods. The literature shows that in recent years there has been an increasing number of quantitative studies focusing on the effects of serious games for people with different disabilities (Bang et al, 2019;van der Kuil et al, 2018). The findings also indicated that descriptive research methods as a non-experimental design and quasi-and true experimental research methods as experimental design were commonly used in quantitative design.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive measures in game-like interfaces can contribute to the early detection of neurological disease [ 26 ]. The study by Bang et al [ 27 ] used an index calculated from in-game metrics to detect children with heterogeneous developmental disabilities, whereas the study by Kim et al [ 28 ] evaluated the use of kinetic variables from the interactions with an SG as a digital biomarker for developmental disabilities.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, efforts have been made to develop cognitive training programs specifically for children with DD in addition to children with typical development [ 9 , 10 ]. DoBrain is a mobilebased cognitive training program designed for children with DD [ 11 ], and targets areas of primary cognitive capacity (attention, orientation, memory), higher-level thinking abilities (problem-solving, reasoning, concept formation), and metaprocessing abilities (executive function, self-awareness). The program consists of multiple levels of games with different levels of difficulty, and only requires simple screen touches as an input.…”
Section: Introductionmentioning
confidence: 99%